Profile of Drug Hypersensitivity Patients Hospitalized in Dr. Soetomo Hospital, Surabaya, Indonesia: Preliminary Data of 6 Months Observation - Isyroqiyyah, Nur Moya; Soegiarto, Gatot; Setiawati, Yuani (Folia Medica Indonesiana, 2019)
Drug hypersensitivity is defined as an untoward response to medication which is noxious and unintended, and which occurs at doses normally used in human either for the prophylaxis, diagnosis, or therapy of disease or for the modification of physiological function. Drug hypersensitivity is common and may cause emergency condition until death. The incidence of drug hypersensitivity-related hospitalizations has usually been assessed within hospitals. The aim of this study is to determine the profile of drug hypersensitivity patients hospitalized at Dr. Soetomo Hospital in 6 months period from January to June 2016. This study was a descriptive retrospective study on medical records of drug hypersensitivity patients hospitalized in Dr. Soetomo Hospital in 6 months period. The patient's demographic data, the type of hypersensitivity reaction, and the final outcome of the hospitalization were collected. Within the 6 months period, there were 16 drug hypersensitivity patients hospitalized in Dr. Soetomo Hospital. Most of them are female (56.25%), and aged between 46-55 years (25%). There were 4 patients (25%) with type I hypersensitivity: urticaria, angioedema and anaphylaxis; while type IV hypersensitivity occured in 12 patients (75%): Stevens-Johnson syndrome, Stevens-Johnson syndrome-Toxic Epidermal Necrolysis overlap, erythroderma, maculopapular drug eruptions, and DRESS. Most of the patients (87.5%) had favorable outcome after hospitalization. There were 16 patients with drug hypersensitivity reaction hospitalized in Dr. Soetomo Hospital, Surabaya in 6 months period. Most of them were female and had type IV hypersensitivity reactions.